Chasing private information - Kacperczyk,MT; Pagnotta,E (The Review of Financial Studies, 2019)
Using over 5000 equity and option trades unequivocally based on nonpublic information about firm fundamentals, we find that commonly used asymmetric information proxies (AIPs) display abnormal values on days with informed trading. Volatility and trading volume are abnormally high, whereas illiquidity is low, both in equity and option markets. Daily returns reflect the sign of private signals but, on average, bid–ask spreads are 10% and 20% lower when informed investors are present in stock and option markets. Market makers’ learning under event uncertainty and the use of limit orders by informed investors help explain these findings. We characterize cross-sectional responses based on the duration of private information and find that informed traders select days with high uninformed volume to trade. Evidence from the U.S. Securities and Exchange Commission (SEC) Whistleblower Reward Program and the Financial Industry Regulatory Authority (FINRA) involvement address potential selection concerns.